OFFSHORE DRILLING AND OIL PRODUCTION PLATFORM METALWORK REPAIR - Vitaly F. Lukyanov; Dmitry V. Rogozin; Vladimir A. Gritsykhin (Advanced Engineering Research)
The underwater repair technique of the offshore drilling platform low-alloy steel support of 38 mm wall thickness is developed. It ensures the required quality of the weld without preheating the base metal.